A scientific-methodical approach to improving the individual skills of young football players - Madaminov Orifjon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article covers information on how to train hard and passionately to become a skilled soccer player.